<< Previous exercise (3.56) | Index | Next exercise (3.58) >>

This exercise is referring to the implementation of fibs in the book which looks like this:

```
(define fibs
(cons-stream 0
(cons-stream 1
(add-streams (stream-cdr fibs)
fibs))))
```

The call to add-streams must read the previous two elements of fibs. When delay is memoized, reading the previous two elements can be done with a lookup, without any additions, and the only addition is the one performed immediately after that. Every adjacent pair of Fibonacci numbers are added only once; the first time. Hence, the total number of additions to get the n-th Fibonacci number is O(n).

If delay were *not* memoized, then the lookup part of the previous two elements would be replaced by a full computation, since every element in a stream besides the very first one is delayed and must be forced every time it is accessed. Hence, "looking up" the values of the two previous Fibonacci numbers now requires all the additions needed to compute those two numbers in the first place.

Let's define A(n) as the number of additions required to obtain the n-th Fibonacci number, assuming that delay is implemented *without* memoization. Then, we have A(n) = A(n-1) + A(n-2), which is exactly the Fibonacci recursion relation. This recursion has the solution A = O(ϕ^n) where ϕ is the golden ratio. Hence, the number of additions when delay is not memoized is exponential.

As an aside, the book also presents an alternative implementation of fibs:

(define (fibgen a b) (cons-stream a (fibgen b (+ a b)))) (define fibs (fibgen 0 1))

This implemention uses an iterative model, not a recursive one, so it takes O(n) additions even when delay is not memoized.

;; First, you can answer the first question after modifying the add-streams (define counter 0) (define (add-streams stream1 stream2) (stream-map (lambda (a b) (begin (set! counter (1+ counter)) (+ a b))) stream1 stream2)) ;; let count-add(fib(n)) = c(n) ;; then c(n+2) = c(n+1) + c(n) + 1 ;; so you can get the c(n) like this (define (count+add n) (+ (* (/ (+ 5 (sqrt 5)) 10) (expt (/ (+ 1 (sqrt 5))2) n)) (* (/ (- 5 (sqrt 5)) 10) (expt (/ (- 1 (sqrt 5))2) n)) (- 1))) ;; so Θ(c(n)) = Θ(φ^n)

;; with memo ;; k = 0, no force ;; k = 1, no force ;; k = 2, 1 force ;; k = 3, 1 force ;; k = 4, 1 force ;; . ;; . ;; . ;; k = n, 1 force ;; total = (n-2) forces ;; no memo ;; for each force, we have to add up all the previous forces for fib and for ;; (stream-cdr fib), so we get fib(k-1) + fib(k-2), but thats exactly fib(k). ;; k = 0, no force ;; k = 1, no force ;; k = 2, 1 force ;; k = 3, 2 force ;; k = 4, 3 force ;; k = 5, 5 force ;; k = 6, 8 force ;; . ;; . ;; . ;; k = n, fib(n) force ;; total = fib(n+2)-1-1, which is equal to the sum of the first n numbers with ;; fib(1) excluded, but thats equal to (phi^(n+2)-psi^(n+2))/sqrt(5) - 2

adams